Updated multi-method estimates of Lake Titicaca's radiocarbon reservoir offset - Eduardo Queiroz Alves; Stéphane Guédron; Christophe Delaere; Mathieu Boudin; Alexandre Chevalier; Tess van den Brande; Gaia Ligovich; Rosa Souza; Peter Eeckhout; Kita Macario (Quaternary Science Reviews, 2025)

Integrating plasmasphere, ionosphere and thermosphere observations and models into a standardised open access research environment: The PITHIA-NRF international project - Anna Belehaki; Ingemar Häggström; Tamas Kiss; Ivan Galkin; Anders Tjulin; Mária Miháliková; Carl-Fredrik Enell; Gabriel Pierantoni; Yin Chen; Gergely Sipos; Sean Bruinsma; Viviane Pierrard; et al. (Advances in Space Research, 2025)

Multiple glacial refugia and contemporary dispersal shape the genetic structure of an endemic amphibian from the Pyrenees - Federica Lucati; Manon Poignet; Alexandre Miró; Audrey Trochet; Fabien Aubret; Laurent Barthe; Romain Bertrand; Teresa Buchaca; Olivier Calvez; Jenny Caner; Elodie Darnet; Mathieu Denoël; et al. (Molecular Ecology, 2020)
Historical factors (colonization scenarios, demographic oscillations) and contemporary processes (population connectivity, current population size) largely contribute to shaping species’ present‐day genetic diversity and structure. In this study, we use a combination of mitochondrial and nuclear DNA markers to understand the role of Quaternary climatic oscillations and present‐day gene flow dynamics in determining the genetic diversity and structure of the newt Calotriton asper (Al. Dugès, 1852), endemic to the Pyrenees. Mitochondrial DNA did not show a clear phylogeographic pattern and presented low levels of variation. In contrast, microsatellites revealed five major genetic lineages with admixture patterns at their boundaries. Approximate Bayesian computation analyses and linear models indicated that the five lineages likely underwent separate evolutionary histories and can be tracked back to distinct glacial refugia. Lineage differentiation started around the Last Glacial Maximum at three focal areas (western, central and eastern Pyrenees) and extended through the end of the Last Glacial Period in the central Pyrenees, where it led to the formation of two more lineages. Our data revealed no evidence of recent dispersal between lineages, whereas borders likely represent zones of secondary contact following expansion from multiple refugia. Finally, we did not find genetic evidence of sex‐biased dispersal. This work highlights the importance of integrating past evolutionary processes and present‐day gene flow and dispersal dynamics, together with multilocus approaches, to gain insights into what shaped the current genetic attributes of amphibians living in montane habitats.

Spatial genetic structure of Lissotriton helveticus L. following the restoration of a forest ponds network - Francis Isselin-Nondedeu; Audrey Trochet; Thomas Joubin; Damien Picard; Roselyne Etienne; Hugo Le Chevalier; Delphine Legrand; Alexandre Ribéron (Conservation Genetics, 2017)

Phytoliths in archaeology: recent advances - Katharina Neumann; Alexandre Chevalier; Luc Vrydaghs (Vegetation History and Archaeobotany, 2017)